Dual targeting negative enrichment strategy for highly sensitive and purity detection of CTCs - Gao, Siying; Li, Xuejie; Hu, Zhiyuan; Wang, Zihua; Hao, Xiaopeng (Frontiers in Chemistry, 2024)
Circulating tumor cells (CTCs) have significant clinical value in early tumor detection, dynamic monitoring and immunotherapy. CTC detection stands out as a leading non-invasive approach for tumor diagnostics and therapeutics. However, the high heterogeneity of CTCs and the occurrence of epithelial-mesenchymal transition (EMT) during metastasis pose challenges to methods relying on EpCAM-positive enrichment. To address these limitations, a method based on negative enrichment of CTCs using specific leukocyte targets has been developed. In this study, aiming to overcome the low purity associated with immunomagnetic beads targeting solely the leukocyte common antigen CD45, we introduced CD66b-modified immunomagnetic beads. CD66b, a specific target for neutrophils with abundant residues, was chosen as a complementary approach. The process involved initial collection of nucleated cells from whole blood samples using density gradient centrifugation. Subsequently, magnetically labeled leukocytes were removed by magnetic field, enabling the capture of CTCs with higher sensitivity and purity while retaining their activity. Finally, we selected 20 clinical blood samples from patients with various cancers to validate the effectiveness of this strategy, providing a new generalized tool for the clinical detection of CTCs.